Analysis of Mathematical Reasoning Ability Viewed from Student Learning Motivation - Hesti Marianah; Fitriyani Hali (Universitas Sembilanbelas November Kolaka, 2020)
This study aims to describe mathematical reasoning abilities in terms of student motivation in class VIII SMP Negeri Satap 1 Lambandia. This type of research is qualitative. The subjects of this study consisted of 20 students of class VIII SMP Negeri Satap 1 Lambandia. The instrument used is a mathematical reasoning ability test consisting of 4 questions, a learning motivation questionnaire consisting of 16 statements, and interview guidelines. The results showed that; 1) The average mathematical reasoning ability of students is 40.78 which is in the fairly low category. Many students who have a high level of ability score is 1 (5%), students with a moderately low ability score of 10 (50%), and many students who have a low ability score are 9 (45%); 2) The number of students with high levels of learning motivation is 7 students (35%), moderate learning motivation is 5 students (25%), and low learning motivation is 8 (40%); 3) Students with high learning motivation have the highest average ability with an average score of 48.66 with quite low criteria, followed by students with moderate and low learning motivation with scores of 40 and 35.15, both of which are in the criteria low. Subjects with high learning motivation are generally able to understand 3 indicators of mathematical reasoning, namely using patterns and relationships to analyze mathematically, estimate the completion process and develop valid arguments using systematic steps. Subjects with moderate and low learning motivation were only able to understand 3 indicators, namely using patterns and relationships to analyze mathematically, estimate the completion process and develop valid arguments using systematic steps. So it can be said that high, medium and low learning motivation has the same level of reasoning ability, namely in the low category.